Commentary: Inquiry: Doing What Comes Naturally (LEARNing Landscapes, 2011)
We are all born with basic habits of mind that enable us to successfully learn about and master our world. Gradually, however, those abilities are sidelined as children progress through school. Inquiry becomes confused with research, and the agency of children as inquirers is lost.This exploration of the meaning of inquiry identifies three elements that are crucial to the process. Choice, curiosity and gut instinct—hardly fodder for educational research or the standardization of curricula—are presented as central to maintaining healthy lifelong learning.
Keywords: inquiry; research; agency; choice; curiosity; gut instinct; lifelong learning